Pelatihan Pengembangan Media Pembelajaran Berbasis Wordwall Di UPT SMP Negeri 2 Bontonompo - Nursakiah, Nursakiah; Ikhbariaty Kautsar Qadry; Randy Saputra Mahmud; Erni Ekafitria Bahar; Abd. Kadir Jaelani; Sitti Rahma Tahir; St. Nur Humairah Halim; Takdirmin; Andi Quraisy; Ahmad Syamsuadi; Mutmainnah (Education and Talent Development Center of Indonesia, 2025)
This training program was initiated due to the limited ability of teachers to develop interactive digital-based learning media aligned with the Merdeka Curriculum. The objective was to enhance teachers’ competence in designing and utilizing Wordwall-based media to support engaging and participatory classroom activities. The training was conducted in both offline and online modes at UPT SMP Negeri 2 Bontonompo, involving 13 teachers. The implementation included lectures, demonstrations, Wordwall creation practices, and mentoring. Evaluation was carried out using pretest and posttest instruments, as well as quality analysis of the developed media. The results indicated a significant improvement in scores, rising from an average of 14.92 (pretest) to 20.38 (posttest), with a Sig. < 0.05. All participants successfully produced one Wordwall-based media relevant to their teaching topics. This activity significantly contributed to improving teachers' skills in integrating technology into instruction and strengthening their digital pedagogical capacity. The program serves as a viable model for ongoing training aimed at promoting technology-integrated learning in schools.